Peran Green Accounting dan Woman On Board terhadap Business Performance pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2018/2022 - Parasdya Pandhu A; Liya Mustahida; Shofiatul Mila (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to provide information on the extent to which Environmental Costs, Environmental Performance, Environmental Activities, and Women on Board influence Business Performance in mining companies listed on the Indonesia Stock Exchange from 2018 to 2022. This is a quantitative study using secondary data obtained from company annual reports and companies participating in PROPER (Program for Pollution Control, Evaluation, and Rating). The purposive sampling method was used to select the sample, resulting in 21 companies observed over a 5-year period. The dependent variable in this study is Business Performance, while the independent variables are Green Accounting (including Environmental Costs, Environmental Performance, and Environmental Activities) and Women on Board. The analysis was conducted using multiple linear regression with the EViews 12 software. The findings are environmental Activities had a positive and significant effect on Business Performance, Women on Board had a negative but insignificant effect on Business Performance, while Environmental Costs and Environmental Performance had a negative but insignificant effect on Business Performance.